Utility and Associated Risk of Pulmonary Embolism Computed Tomography Scans in the Michigan Lupus Cohort. Issue 3 (March 2016) - Kado, Ruba; Siegwald, Emily; Lewis, Emily; Goodsitt, Mitchell M.; Christodoulou, Emmanuel; Kazerooni, Ella; McCune, W. Joseph
Abstract : Objective: Systemic lupus erythematosus patients are frequently evaluated for chest pain and may have multiple pulmonary embolism (PE) computed tomography (CT) scans. This study was undertaken to determine the incidence of pulmonary embolism in the University of Michigan Lupus Cohort patients who have undergone PE CT scans and to estimate the associated increased risk of breast and lung cancer from radiation exposure. Methods: We reviewed records of patients in the University of Michigan Lupus Cohort (n = 854) and determined the number and outcome of PE CT scans. Radimetrics software was used to perform individualized calculations of radiation dose to the lung and breast of each patient. We used this dose information, the patient's age at the time of scan, and risks according to the Biological Effects of Ionizing Radiation, report VII, to estimate the increased incidence risks of breast and lung cancer. Results: A total of 182 of 856 patients (21%) underwent 357 PE CT scans. The overall rate of positivity was 7.5%. For patients undergoing their first through third scans, the rate of positivity for PE was 8.8%, whereas patients undergoing their fourth through tenth scans had 1.6% positivity. The highest increase in incidence risk was 0.87% for breast and 0.62% for lung. Conclusion: Patients with multiple previous PE CT scans had lower likelihood of a positive result on subsequent scans and higher risks of malignancy. The magnitude of risk should not discourage performance of PE CT when clinically indicated.